2014
DOI: 10.1016/j.rbmo.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity before IVF and ICSI cycles in infertile obese women: an observational cohort study

Abstract: This study assessed the relationship between regular physical activity and reproductive performance in obese infertile patients who receive assisted reproduction cycles with stable bodyweight. A total of 216 obese infertile women at their first fresh assisted reproduction attempt with stable body mass index (BMI) and available data on their physical activity carried out up to the beginning of the treatment cycle were enrolled in this observational cohort study. Clinical and biological data were recorded and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 35 publications
2
47
0
10
Order By: Relevance
“…Are there some other fertility factors that put them in the Bgood prognosis^group? For example, it has been shown that chances to obtain a pregnancy and live birth are threefold higher in obese infertile patients who are regularly physically active in comparison to those who are not, irrespective to their body weight loss [45]. We investigated irregular menstrual cycle rate in order to discover whether PCO syndrome represents a risk for an LGA singleton, and we found no connection to LGA.…”
Section: Discussionmentioning
confidence: 95%
“…Are there some other fertility factors that put them in the Bgood prognosis^group? For example, it has been shown that chances to obtain a pregnancy and live birth are threefold higher in obese infertile patients who are regularly physically active in comparison to those who are not, irrespective to their body weight loss [45]. We investigated irregular menstrual cycle rate in order to discover whether PCO syndrome represents a risk for an LGA singleton, and we found no connection to LGA.…”
Section: Discussionmentioning
confidence: 95%
“…Results of previous studies on physical activity and outcomes of assisted reproduction have been inconsistent, with two studies finding a beneficial effect (Evenson et al ., 2014; Palomba et al ., 2014), two finding no effect (Kucuk et al ., 2010; Moran et al ., 2011), and one finding a detrimental effect (Morris et al ., 2006). The accuracy and time frame of physical activity assessment could be one explanation for the heterogeneous results across studies.…”
Section: Discussionmentioning
confidence: 99%
“…A third study (Moran et al ., 2011), a small trial that randomized overweight women to a lifestyle intervention, including a reduced energy diet and a home-based physical conditioning and walking programme before IVF, observed no differences in pregnancies or live births compared with a group receiving standard treatment. Finally, the two most recent cohort studies showed that regular physical activity carried out before an assisted reproduction cycle was related to improved live birth rates in a cohort of obese patients (Palomba et al ., 2014) and improved clinical pregnancy rates in a general IVF population (Evenson et al ., 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies failed to demonstrate a relationship between PA and semen quality [11,12]. In women, moderate PA increased fecundity parameters and live birth rates, regardless of body mass index (BMI) [13,14]—even during assisted reproductive treatment [1517]. However, vigorous activity has been associated with lower semen quality in men [1820] and decreased fertility in women [2123].…”
Section: Introductionmentioning
confidence: 99%